Bowel Obstruction Caused by Persimmon Phytobezoars: A Case Report - Mohammadi, Amir; Mojtahedzadeh, Mojataba; Ahmadi, Arezoo; Imanipour, Mohammad Hossein; Saghafi, Fatemeh; Soltaninejad, Sareh; Sahebnasagh, Adeleh (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: The term phytobezoar refers to a trapped mass in the gastrointestinal tract caused by the agglomeration of indigestible ingested plant materials, including fibers, skins, and seeds. A persimmon phytobezoar is formed after the frequent consumption of persimmons. The clinical manifestations of persimmon phytobezoars are similar to other phytobezoars and depend on the localization and size of the trapped mass. Case Presentation: Here, we presented a 57-year-old male with persimmon phytobezoars, which finally led to small bowel obstruction. The patient was referred to the emergency room with complaints of severe abdominal pain and frequent vomiting. The patient underwent laparotomy surgery that led to the removal of a portion of his ileum. Conclusion: Overindulgence in taking persimmon can lead to formation of phytobezoar and subsequent obstruction of small intestinal. Persimmon phytobezoars are difficult to break up into pieces because of containing tannins, cellulose, hemicellulose, and lignin.